Downregulation of miR‐20b‐5p facilitates Mycobacterium tuberculosis survival in RAW 264.7 macrophages via attenuating the cell apoptosis by Mcl‐1 upregulation. Issue 4 (30th October 2018) - Zhang, Defeng; Yi, Zhengjun; Fu, Yurong
Abstract: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis (Mtb). The interaction between Mtb and macrophages, which is regulated by microRNAs, determines the development of TB. However, the function of microRNA‐20b‐5p (miR‐20b‐5p) in RAW 264.7 macrophages against Mtb remains unknown. In this study, we analyzed the expression level of miR‐20b‐5p in macrophage responses to Mtb infection and exosomes derived from macrophages after Mtb infection. MiR‐20b‐5p mimics and inhibitor were, respectively, transfected to evaluate the effect of miR‐20b‐5p on Mtb and macrophages. In addition, the targets of miR‐20b‐5p were predicted by a bioinformatics analysis. The macrophages were respectively transfected with miR‐20b‐5p mimics and inhibitor to determine the messenger RNA expression levels of the targets by reverse transcription‐polymerase chain reaction assay. The results revealed that the miR‐20b‐5p expression level was decreased in the infected macrophages at different times. MiR‐20b‐5p was shown in the exosomes released from macrophages infected with Mtb. Upregulation of the miR‐20b‐5p level suppressed the survival of Mtb in macrophages, while downregulation of the miR‐20b‐5p level enhanced the survival of Mtb in macrophages. Overexpression of miR‐20b‐5p decreased the cell viability and induced apoptosis in Mtb‐infected macrophages, while underexpression of miR‐20b‐5p increased the cell vitality and attenuated apoptosis in Mtb‐infected macrophages. The bioinformatics analysis revealed that Mcl‐1 was a target of miR‐20b‐5p. MiR‐20b‐5p negatively regulated the expression of Mcl‐1. Overall, this study is the first to demonstrate the effect of miR‐20b‐5p on Mtb infection and present miR‐20b‐5p and exosomes as the potential therapeutic targets of TB. Abstract : Mycobacterium tuberculosis (Mtb) infection downregulated the microRNA‐20b‐5p (miR‐20b‐5p) transcript in RAW 264.7 macrophages in a time‐dependent manner. MiR‐20b‐5p was sorted and assembled into the exosomes derived from Mtb‐infected RAW 264.7 macrophages. MiR‐20b‐5p negatively regulated the survival of Mtb in RAW 264.7 macrophages, in part, possibly through the mechanism of targeting the antiapoptosis gene Mcl‐1 to inhibit apoptosis.